Phytosociological analysis of Tropical Rain Forest and determination of key-species to recovery of degraded area based through the importance value index - Salomão, Rafael de Paiva; Santana, Antônio Cordeiro; Brienza Júnior, Silvio; Gomes, Vitor Hugo Freitas (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2012)
In the National Forest of Saracá-Taquera, Para State, the bauxite mining is made in open pits. The mining operations involve since the complete removal of the tropical rain forest to the land restoration by heterogeneous reforestation where are employed on average 80 species. The objective of this paper is to provide an index of horizontal phytosociology dummy (IHP), calculated through the same variables used to obtain the importance value index (IVI), by ranking tree species sampled in the inventories of the tropical rain forest in ecologic categories of high, medium and low priorities. The phytosociological inventories done in the Saracá plateau recorded 23,166 individuals, summing 796 species and 58 families. The adequacy of the factor analysis was determined by the tests of Bartlett, which evaluated the overall significance of the correlation matrix and shows that the correlations are significant to the 1% probability level, and Kaiser-Meyer-Olkin (KMO), which shows that the variables are correlated and that the factor model has a good fitness to the data set. The statistical tests validated the data set for use of multivariate analysis technique, and therefore for the construction of the IHP, which selected 65 key species for use in forest restoration purposes, against only six indicated by the IVI.
Keywords: Species selection; Dense tropical forest; Forest restoration; Bauxite mining; Multivariate analysis; Amazonia